Are we human? notes on an archeology of design - Colomina, Beatriz 1952-; Wigley, Mark 1956- (Lars Müller Publishers, 2016)
Aus dem Inhalt: invention of the human - design of health - human-centered-design - designing the body
Keywords: Anthropologie; Mensch -- Motiv; Archäologie; Theorie; Design